1983
DOI: 10.1111/j.1365-2818.1983.tb04227.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoultramicrotomy versus plastic embedding: comparative immunocytochemistry of rat anterior pituitary cells

Abstract: SUMMARY The anterior pituitary of the rat is used as a model for the study of the effects of freezing or plastic embedding on the maintenance of antigenicity. Rat anterior pituitaries are fixed in 2.5% glutaraldehyde in 0.1 m phosphate buffer pH 7.4. Some of the blocks are post‐fixed before being divided into two lots. One batch is frozen, while the other is dehydrated and embedded. The indirect antibody enzyme method is applied to ultrathin sections obtained by cryoultramicrotomy after freezing or by sectioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…These results, which clearly show the restricted pres ence of rGH-RBP expression in discrete adult rat pitu itary cells, were obtained using nonradioactive in situ hybridization and immunocytology performed on ultrathin frozen sections; these methods have been shown to be highly sensitive [21,23,24,26,27], The controls carried out in our study indicated the specificity of the in situ hybridization for the detection of GH-RBP mRNA trans cripts and of immunocytology for the detection of the GH-RBP protein. In addition, visualization of the intense signal produced by the rGH-RBP mRNAs and rGH-RBP immunoreactivity in the hepatocytes, where the presence GH PRl LH-FSH NS Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, which clearly show the restricted pres ence of rGH-RBP expression in discrete adult rat pitu itary cells, were obtained using nonradioactive in situ hybridization and immunocytology performed on ultrathin frozen sections; these methods have been shown to be highly sensitive [21,23,24,26,27], The controls carried out in our study indicated the specificity of the in situ hybridization for the detection of GH-RBP mRNA trans cripts and of immunocytology for the detection of the GH-RBP protein. In addition, visualization of the intense signal produced by the rGH-RBP mRNAs and rGH-RBP immunoreactivity in the hepatocytes, where the presence GH PRl LH-FSH NS Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The grids were stained with uranyl acetate, embed ded in methyl cellulose [21], and examined with a Philips CM 10 electron microscope at 80 kV. The morphological characteristics of pituitary cells after cryoultramicrotomy have been found to be simi lar to those of epoxy resin-embedded tissue [26]; the somatotrophs contain secretory granules 350 nm in diameter, and their endoplas mic reticulum consists of regular and parallel cisternae; the lactotrophs contain secretory granules of irregular shape, measuring 400-700 nm. and their endoplasmic reticulum takes the form of regular and parallel cisternae; the gonadotrophs contain secretory granules of 200-300 nm, and occasionally 600-700 nm, in diameter, and in many cases their endoplasmic reticulum is vesicular, the thyrotrophs contains dense secretory granules uniformly smaller than 100 nm: the corticotrophs are characterized by their stellate shape and their small (200 nm) secretory granules.…”
Section: Immunocytologymentioning
confidence: 99%
“…Although the presence of GHlike immunoreactivity (GH-LI) in somatotrophs has been observed with all the techniques described below, the localization of immunoreactivity was not exactly the same in each case. Using preembedding methods (Dachew and Dubois, 1976) or ultra-thin frozen sections (Hemming et al, 1989), immunoreactivity could be detected in the secretory granules where GH is stored, as well as in the endoplasmic reticulum where GH is synthesized. After embedding, using hydrophilic (Roson and Beiras, 1991) or epoxy (Li et al, 1977;Moriarty, 1973;Nakane, 1970) zymatic detection system and an intermediate sensitivity.…”
mentioning
confidence: 99%
“…Stockholm, Sweden) fitted with a cryokit as described by Tokuyasu [37]. The ultrathin sections were incubated consecutively for lO-min periods with (a) normal sheep serum (dilution '/ioo); (b) anti-hpGRF serum (dilution from 2x I0~4to2x I0'6), or anti-hGH rabbit serum (dilutions 2xl0"3 and 2xl0'6); (c) sheep antiserum to rabbit-y -globulin (dilution 2xl0~4); (d) peroxidase-antiperoxidase com plex (dilution 2x 10'4); (e) 4-chloro-l-naphthol (ICN Pharmaceuti cal Plainview, N.Y.) solution in Tris-buffered saline as previously described [18] for 3 min -this solution was used with 0.01% hydro gen peroxide as enzymatic substrate; (0 1% phosphate-buffered os mium tetroxide for 10 min. …”
mentioning
confidence: 99%